RETRACTED: Impact of academic cheating and perceived online learning effectiveness on academic performance during the COVID-19 pandemic among Pakistani students - Malik, Aamir Abbas; Hassan, Mehdi; Rizwan, Muhammad; Mushtaque, Iqra; Lak, Tauqeer Ahmed; Hussain, Mussarat (Frontiers in Psychology, 2023)
Abstract Objective: The study was conducted to examine academic cheating behaviors and perceived online effectiveness on academic performance during the period of COVID-19 among schools, colleges, and university students in Pakistan. Methodology: A cross-sectional research design was used in the current study. Convenience sampling was used to collect the data. The study included a total sample of N= 8590 students, with males (n= 3270, 38%) and females (n= 5320, 61%) participating. The data was divided into three categories: high schools (n = 1098, 12.7%), colleges (n = 4742, 55.2%), and universities (n = 2570, 32.1%). School students had an average age of (M = 15, SD = 4.65), college students had an average age of (M = 20, SD = 5.64), and university students had an average age of (M = 24, SD = 5.01). Result: The results indicated that 60% of students admitted to cheating during online exams most of the time; 30% of students admitted to cheating at least once during an online exam. The study found that students (from high school, college, and university) obtained higher grades in online exams as compared to physical exams. Furthermore, significant gender differences were found on the scales of online learning effectiveness in school, college, and university students (t = 2.3*, p =.05 vs. t = 4.32**, p =.000 vs. t = -3.3*, p =.04). Similarly, on the scale of academic performance, students have significant gender differences. Multivariate regression analysis confirms that students' 26% academic performance was increased due to cheating (F (2, 8588) = 16.24, p.000). Students believe online learning is effective because academic grades are easily obtained. Conclusion: Cheating is more common and easier in online courses, according to more than half of respondents, and they take advantage of this. Academicians are heavily encouraged to develop morality and ethics in their students so that their institutions can produce ethical professionals for the educational community.